Hubungan Stres Pengasuhan Dengan Resiliensi Orang Tua Anak Leukemia di RSUD Arifin Achmad - Ditha Paulina Sembiring; Riri Novayelinda; Yufitriana Amir (SEHATI: Jurnal Kesehatan, 2025)
Leukemia in children is a traumatic experience that impacts the family, especially parents. Severe symptoms increase the burden of caregiving and can trigger stress, which is influenced by parental resilience. This study aims to determine the relationship between parenting stress and the resilience of parents of children with leukemia at Arifin Achmad Pekanbaru Hospital. Method: This research uses a correlational design with a cross-sectional method. The research sample consisted of 78 respondents, namely parents of children with leukemia. This research's bivariate analysis used the Fisher's Exact Test. Results: The majority of respondents were aged 26-35 years (early adulthood), namely 40 respondents (51.3%), 47 respondents (60.3%) were female, 31 respondents (39.7%) had completed tertiary education, came from outpatient rooms, namely 52 respondents (66.7%). The results of statistical tests showed that there was a significant relationship between parenting stress and the resilience of parents of children with leukemia at Arifin Achmad Regional Hospital with p-value = 0.000. Conclusion: Parenting stress has a significant influence on the resilience of parents of children with leukemia at Arifin Achmad Hospital Pekanbaru